Nitric Oxide Synthase Simple Enzyme-Complex Roles - Soheil Saeedi Saravi, Seyed (IntechOpen, 2017)
Nitric Oxide Synthase - Simple Enzyme-Complex Roles provides information on nitric oxide synthase, a biomolecule of key importance for the different biological systems, including central and peripheral nervous, cardiovascular, and reproductive systems. With recent links to the role of nitric oxide in the reactions that can impact cell signaling, and discoveries surrounding the complex role of nitric oxide synthase that have increased research attention across the fields of cell and molecular biology, physiology, pharmacology, toxicology, neuroscience, cardiology, urology, and endocrinology, this book tries to provide a comprehensive overview of biology/pathobiology of nitric oxide synthases and a perspective from possible therapeutic indication of the enzyme inhibitors.